Retinal injuries secondary to consumer laser devices in children (Ukrainian Journal of Ophthalmology, 2026)
Background: In recent years, increased incidence of retinal injuries secondary to consumer laser devices (predominantly, pointers and those used at disco clubs) in children and adolescents have been observed.Purpose: To review the clinical features and structural retinal changes in the macula in pediatric patients following an injury secondary to laser ‘toys’.Materials and Methods: We retrospectively reviewed charts of 5 pediatric patients with retinal laser-induced burns (3 patients with fresh burns, and 2 patients who had a burn injury 1 year and 5 years before). Three patients, one patient and a 16-year-old girl (patient No. 5) received retinal burns from laser pointer, laser flashlight and at a disco club, respectively. On fundus examination, a blurred macular reflex, and 1 to 3 macular foci with pigmentation at the periphery of these foci were noted in three patients with 3 patients with fresh burns. In addition, in patient No. 5, an extensive round-shaped retinal hemorrhage was visualized, and the OCT demonstrated high optical density regions in the fovea under the inner limiting membrane, perifocal areas of thickened internal retinal layers the and loss of the retinal layer structure. In the patient who had a burn injury 5 years before, small foci of RPE atrophy similar to that of retinitis solaris were seen.Results: Patients with fresh burns received systemic and topical antitoxic, dehydration and antioxidant therapy. Laser posterior hyaloidotomy was performed in the patient with retinal hemorrhage. After treatment, in all patients, visual acuity improved substantially from 0.4 with myopic correction to 0.5-0.7.Conclusion: Although complete restoration of retinal foveal structure following pediatric injuries secondary to consumer laser products seems not possible, their timely comprehensive treatment enable high functional outcomes for these patients.
Keywords: retina; laser burns; children